2022
DOI: 10.2174/1574888x16666210907164046
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stem/Stromal Cells Potential to Treat Organ Disorders; An Emerging Strategy

Abstract: : Currently, mesenchymal stem/stromal cells (MSCs) have attracted growing attention in the context of cell-based therapy in regenerative medicine. Following the first successful procurement of human MSCs from bone marrow (BM), these cells isolation has been conducted from various origins, in particular, the umbilical cord (UC). Umbilical cord-derived mesenchymal stem/stromal cells (UC-MSCs) can be acquired by a non-invasive plan and simply cultured, and thereby signifies their superiority over MSCs derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…UC-MSCs can be obtained via a non-invasive strategy and easy cultured, thus offering their advantage over other types of MSCs for therapeutic objectives. Because of their unique characteristics, such as self-renewal, multipotency, and availability simultaneous with their immunosuppressive capability and lesser ethical worries, UC-MSCs treatment is defined as hopeful curative choices in cell-based treatments [ 113 ]. HUC-MSC-EXOs, acquired by extensively expanding hUC-MSCs in vitro, is convenient to extract, store, and transport, lower in immunogenicity, and better in biocompatibility.…”
Section: Different Types Of Msc-exos As Mirnas Delivery Systems In Di...mentioning
confidence: 99%
“…UC-MSCs can be obtained via a non-invasive strategy and easy cultured, thus offering their advantage over other types of MSCs for therapeutic objectives. Because of their unique characteristics, such as self-renewal, multipotency, and availability simultaneous with their immunosuppressive capability and lesser ethical worries, UC-MSCs treatment is defined as hopeful curative choices in cell-based treatments [ 113 ]. HUC-MSC-EXOs, acquired by extensively expanding hUC-MSCs in vitro, is convenient to extract, store, and transport, lower in immunogenicity, and better in biocompatibility.…”
Section: Different Types Of Msc-exos As Mirnas Delivery Systems In Di...mentioning
confidence: 99%
“…However, depending on the tissue, such as the brain or heart, it is difficult to separate stem cells from the living tissue and for use as treatment. In recent years, MSCs have been the focus of attention because they are relatively easy to extract from various tissues, including the bone marrow, adipose tissue, placenta, umbilical cord, synovium, and pulp [ 146 , 147 , 148 , 149 , 150 ]. Furthermore, they can also differentiate into ectoderm-derived nerve cells and glial cells that perform functions such as supporting nerve cells and endoderm-derived hepatocytes [ 151 , 152 , 153 , 154 ].…”
Section: Mesenchymal Stem Cells (Mscs) For Regenerationmentioning
confidence: 99%
“…It has been shown that MSC-DEs can modulate hyperoxia-induced retinopathy, suggesting a new safe non-cellular therapy for ROP ( Moisseiev et al, 2017 ). Also, researchers have demonstrated the influential role of microglia derived-exosome in treating retina-related diseases ( Ebneter et al, 2017 ; Xu et al, 2019 ; Ahani-Nahayati et al, 2021b ). Injection of microglia derived exosome into vitreous has induced down-regulation of VEGF, TGF-β and suppresses apoptosis of photoreceptor, indicating the therapeutic application of exosome in ROP ( Xu et al, 2019 ).…”
Section: Exosome Therapy In Other Ocular Disordersmentioning
confidence: 99%